What is community justice? : case studies of restorative justice and community supervision - Clear, Todd R.; Karp, David R., 1964- (Thousand Oaks [CA] : Sage Publications, 2002)
Past methods of probation and parole supervision have largely relied on caseworkers who monitor their "clients" as well as they can. But, as numbers of "clients" increase, studies indicate that this model is ineffectual. The time has come to significantly rethink the approaches to community supervision. As described in What Is Community Justice?, the aim of the new efforts is to explicitly integrate the community and the criminal justice process in probation programs. There are five key goals that this book addresses to achieve this end: · The building of partnerships between community supervision agencies and the community · Expanding the "client" definition to include the victim of crime, the family of the offender, and the community itself · Focus on places: agencies must take into account important local differences in neighborhoods · Preventing problems between the community and the client rather than reacting to them · Adding value to community life This book addresses the specific ways of achieving these goals by presenting six case studies of probation programs that represent a practical side of the community justice ideal. What emerges is a provocative and enlightening new approach to the problems of probation and parole.
Cover; Contents; Preface; The Community Justice Frontier: An Introduction; 1 -- Ventura County and the Theory of Community Justice; 2 -- Neighbourhood Probation Offices in Maricopa County, Arizona; 3 -- The Offender/Community Encounter; 4 -- Restorative Justice, Reparation, and the Southside Project; 5 -- Reinventing Probation and Reducing Youth Violence; 6 -- Deschutes County, Oregon; 7 -- Afterword; Index; About the Editors
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Community-based corrections -- United States -- Case studies; Alternatives to imprisonment -- United States -- Case studies; Criminal justice, Administration of -- United States -- Citizen participation -- Case studies; Services correctionnels communautaires -- États-Unis -- Études de cas; Emprisonnement -- Alternative -- États-Unis -- Études de cas; Justice pénale -- Administration -- États-Unis -- Participation des citoyens -- Études de cas; SOCIAL SCIENCE -- Penology; Alternatives to imprisonment; Community-based corrections; Criminal justice, Administration of -- Citizen participation; United States; Case studies